Damage accumulation during high temperature fatigue of Ti/SiCf metal matrix composites under different stress amplitudes. (July 2021) - Wang, Ying; Xu, Xu; Zhao, Wenxia; Li, Nan; McDonald, Samuel A.; Chai, Yuan; Atkinson, Michael; Dobson, Katherine J.; Michalik, Stefan; Fan, Yingwei; Withers, Philip J.; Zhou, Xiaorong; et al.
Abstract: The damage mechanisms and load redistribution taking place under high temperature (350 °C), high cycle fatigue (HCF) of TC17 titanium alloy/unidirectional SiC fibre composites have been investigated in situ using synchrotron X-ray computed tomography (CT) and X-ray diffraction (XRD) under two stress amplitudes. The three-dimensional morphology of the fatigue crack and fibre fractures has been mapped by CT. At low stress amplitude, stable growth occurs with the matrix crack deflecting by 50-100 µm in height as it bypasses the bridging fibres. At higher stress amplitude, loading to the peak stress led to a burst of fibre fractures giving rise to rapid crack growth. Many of the fibre fractures occurred 50-300 µm above/below the matrix crack plane during rapid growth, contrary to that in the stable growth stage, leading to extensive fibre pull-out on the fracture surface. The changes in fibre loading, interfacial stress, and the extent of fibre-matrix debonding in the vicinity of the crack have been mapped over the fatigue cycle and after the rapid crack growth by XRD. The fibre/matrix interfacial sliding extends up to 600 µm (in the stable-growth zone) or 700 µm (in the rapid-growth zone) either side of the crack plane. The direction of interfacial shear stress reverses over the loading cycle, with the maximum frictional sliding stress reaching 55 MPa in both regimes. In accordance with previous studies, it is possible that a degradation in fibre strength at elevated temperature is responsible for bursts of fibre fracture and rapid crack growth under higher stress amplitude. Graphical abstract: Image, graphical abstract